Guide to financial markets - "Levinson, Marc" (London, 2007)
The definitive guide to why different financial markets exist and how they operate. Extensively revised and updated, the 4th edition of this best-selling book, brings the reader right up to speed with the latest developments in financial instruments and provides a clear and incisive guide to this complex world that even those who work in it often find hard to understand. With chapters on the markets that deal with money, foreign exchange, equities, bonds, commodities, financial futures, options and other derivatives, it looks at why these markets exist, how they work and who trades in them, and it gives a run-down of the factors that affect prices and rates. Business history is littered with disasters that occurred because people involved their firms in financial markets they didn't properly understand. Read this book and you and your company won't be new additions to this list. A fabulous source of reference for anyone wishing to understand financial markets - there is no better guide.
Keywords: financial economics